Haematological emergencies. (May 2021) - Curto-Garcia, Natalia; Saunders, Jamie; Doyle, Andrew
Abstract: This article summarizes the management of common haematological emergencies. Patients with haematological disorders may have associated co-morbidities and/or be being given chemotherapy treatment, which can be daunting to doctors who have not previously encountered these clinical situations. Laboratory data interpretation, familiarity with disease-associated complications and good clinical skills are essential for the diagnosis and management of haematological emergencies. This review aims to discuss the key concepts in the diagnosis and management of frequently encountered emergencies in these patients.